2015
DOI: 10.1111/ijfs.12878
|View full text |Cite
|
Sign up to set email alerts
|

Effects of external shear forces on crystallisation kinetics of model fat blends

Abstract: Summary The effects of different shearing conditions on the crystallisation of cocoa butter (CB) with the addition of other confectionery ingredients (sugar and lecithin) were investigated. Differential scanning calorimetry (DSC), X‐ray diffraction (XRD) and polarised light microscopy (PLM) were conducted to measure the thermal, polymorphic and microstructural properties, of these mixtures, respectively. Both shearing conditions and ingredients have a pronounced impact on the thermal and polymorphic behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…This analysis revealed that CB samples processed under RS and LS had crystal sizes of about 8 to 8.5 µm 2 and those with the addition of monostearate had crystal sizes of 11.4 to 13.3 µm 2 . The increase in crystal size for commercial fats such as CB with the addition of an emulsifier has been previously observed with the addition of lecithin to CB and palm oil [14,31]. This increase is generally thought to occur because emulsifiers form thermodynamically favorable micellular structures that can lower the energy barrier for nucleation [32].…”
Section: Resultsmentioning
confidence: 84%
“…This analysis revealed that CB samples processed under RS and LS had crystal sizes of about 8 to 8.5 µm 2 and those with the addition of monostearate had crystal sizes of 11.4 to 13.3 µm 2 . The increase in crystal size for commercial fats such as CB with the addition of an emulsifier has been previously observed with the addition of lecithin to CB and palm oil [14,31]. This increase is generally thought to occur because emulsifiers form thermodynamically favorable micellular structures that can lower the energy barrier for nucleation [32].…”
Section: Resultsmentioning
confidence: 84%
“…A statistical comparison of crystal sizes showed that the fast-cooled samples at 200 s –1 shear had significantly smaller crystal sizes compared to those of the slow-cooled samples made with the same LLL/OOO ratio. It has been previously reported that the increase in cooling rate and the presence of shearing lead to a decrease in the size of crystals. The smaller size of crystals observed in samples cooled faster at the same shear rate of 200 s –1 (Table ) could be explained by the viscosity changes and nucleation rate of crystals under different cooling rates .…”
Section: Resultsmentioning
confidence: 99%
“…While lecithin has been known to control crystallization in chocolate as well as other fat‐based products, the exact mechanism is not yet known (Ribeiro et al ., ). One possibility is by its action of delaying the formation of more stable polymorphs of cocoa butter (Shi & Maleky, ). As regards to the effect of CITREM, high concentrations of the additive (starting at about 7.5%) were more sufficient in preventing any polymorphic transformation of tristearin as opposed to lower concentrations, even after a few weeks of storage (Garti et al ., ).The effect of MAGs on the crystallization of chocolate and compound chocolate has not been fully investigated as compared to DAGs.…”
Section: Resultsmentioning
confidence: 99%